‘No, I do not suffer from it’: the analysis of the manipulation of the subjectivity of the executive woman in the rise of the career - Elem Rabelo Duarte; Shalimar Gallon (BBR: Brazilian Business Review)
The insertion of women in executive positions has grown, but they need to adapt to the impositions of management to achieve and preserve a successful career. In this context, this article sought to analyze the manipulation of the subjectivity of executive women in career advancement. For this purpose, a descriptive study was carried out with 14 executive women working in national and multinational companies, with the information being analyzed using the content analysis technique. The results show that the executives conform to the impositions of the position and try to adapt themselves to exemplary behavior. They create defense strategies to deal with disposability, personal resignations and justify taking their place. With a support team to handle their demands, they deny the labyrinths of the trajectory, evidencing the presence of the queen bee phenomenon, and reproduce a behavior that privileges masculinities in organizations.